(untitled) (World Journal of Vocational Education and Training, 2020)
The recent pandemic raised new issues of hygiene and safety, regarding large parts of population, especially considering the more vulnerable groups of societies. Among these groups, special care is required for pupils with mental, physical and/or functional disabilities. The latter category of disabilities is usually caused to immigrant pupils, due to language barriers that hinder the proper teaching and learning process. Along with the new hazards, old ones haven’t disappeared, like the danger of traffic accidents. Accordingly, this paper presents two safety courses for pupils of secondary education with disabilities, the one regarding traffic education and the other issues of personal hygiene, that aim at achieving the equal and autonomous living of vulnerable groups of pupils who are subject to multiple discrimination. These two courses are described in sufficient details for being implemented by the interested educators of Special Vocational Education, after a pilot application in a vocational school of Secondary Special Education, at the city of Elefsis, Greece. This pilot application proved the validity of the described herein educational project, but its success should be enhanced by the dissemination of the results to the whole local community.